Pengaruh Soft Skill dan On The Job Training Serta Work Motivation Terhadap Kinerja Karyawan Pada PT. Palma Gemilang Kencana Jambi - Nainggolan, Ester; Prayudi, Ahmad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Abstract The purpose of this research is to determine the influence of Soft skills, On-the-job training, and Work motivation on employee performance at PT. Palma Gemilang Kencana in Jambi, which consists of 81 people, with the total population being used as a sample through saturation sampling. The data collection method in this study is a questionnaire and library research. The analysis uses descriptive methods and multiple linear regression with a significance level of 0.05. The results of the F test show that Soft skills, On-the-job training, and Work motivation together have a positive and significant effect on the dependent variable, which is employee performance. Based on the determination coefficient (R2) test, the Adjusted R Square value is 0.612%, meaning that the quality of Soft skills, On-the-job training, and Work motivation affects employee performance by 61.2%, and the remaining 38.8% can be explained by other factors that were not examined in this study. Keywords: Soft skill, On the job training, Work motivation, employe performance